Conference Social Policy and Social Work in the Modern World: Problems and Strategies, State University of St Petersburg, 27 th February - Guerreiro, MD (Conference Social Policy and Social Work in the Modern World: Problems and Strategies, State University of St Petersburg, 27 th February, 2015)
This communication aimed to present the situation of Portuguese society with regard to a set of socio-structural characteristics and their social problems. It also sought to analyze the main policy measures addressing problems such as disadvantaged families, children at risk, domestic violence and care for the elderly.